Performance Analysis of LMS, RLS, CMA Algorithms for Beamforming in Smart Antenna Systems - Mane, Mrs. Sunita V.; Bombale, Dr. Uttam L. (International journal of recent technology and engineering, 2019)
Smart antenna systems strengthen wireless mobile communication, with enhancement over conventional systems, by projecting the signal power in narrow beams towards the desired users and suppressing the signal power towards unwanted users or interferers. Different DOA estimation and beamforming algorithms play crucial role in smart antenna system. In beamforming algorithms, using different techniques complex weights are calculated and applied to the signals from the smart antenna array elements to enhance signals of interest and suppress signals not of interest. In this article Least Mean Square(LMS) technique, Recursive Least Square(RLS)technique and Constant Modulus (CMA)technique adaptive beamforming algorithms are implemented, analyzed and compared using MATLAB simulations to help users to choose amongst them as per the their need, ease and suitability.